Design and Analysis of a New Magnetorheological Damper for Generation of Tunable Shock-Wave Profiles - Jong-Seok Oh; Tae-Hoon Lee; Seung-Bok Choi (Shock and Vibration, 2018)
A new impact testing system with an integrated magnetorheological (MR) damper is proposed, and its dynamic characteristics are analyzed. The testing system consists of a velocity generator, impact mass, test mass, spring, and MR damper. In order to tune the dual shock-wave profile, a dynamic model was constructed, and the appropriate design parameters of the MR damper were then determined to produce the required damping force. Following this, an impact testing system was constructed to evaluate the design analysis and field-dependent dual shock-wave profiles. The experimental results of impact test showed that the dual shock-wave profile can be altered by changing the intensity of the magnetic field.